Female Gut and Genital Tract Microbiota-Induced Crosstalk and Differential Effects of Short-Chain Fatty Acids on Immune Sequelae - Amabebe, Emmanuel; Anumba, Dilly O. C. (Frontiers in Immunology, 2020)
The gut and genital tract microbiota of females represent very complex biological ecosystems that are in continuous communication with each other. The crosstalk between these two ecosystems impacts host physiological, immunological and metabolic homeostasis and vice versa. The vaginal microbiota evolved through a continuous translocation of species from the gut to the vagina or through a mother-to-child transfer during delivery. Though the organisms retain their physio-biochemical characteristics while in the vagina, the immune responses elicited by their metabolic by-products appear to be at variance with those in the gut. This has critical implications for the gynaecological, reproductive as well as overall wellbeing of the host and by extension her offspring. The homeostatic and immunomodulatory effects of the bacterial fermentation products (short chain fatty acids, SCFAs) in the gut are better understood compared to the genital tract. While gut SCFAs prevent a leakage of bacteria and bacterial products from the gut in to circulation (leaky gut) and consequent systemic inflammation (anti-inflammatory/protective role); they have been shown to exhibit dysbiotic and proinflammatory effects in the genital tract that can lead to unfavourable gynaecological and reproductive outcomes. Therefore, this review was conceived to critically examine the correlation between the female gut and genital tract microbiota. Secondly, we explored the metabolic patterns of the respective microbiota niches; and thirdly, we described the diverse effects of products of bacterial fermentation on immunological responses in the vaginal and rectal ecosystems.